MEMPERKUAT EMPATY MAHASISWA:Studi pada Mahasiswa PIAUD UIN Sunan Kalijaga Yogyakarta - Sakila, Siti Risda; Rohmah, Lailatu; Nurhayati, Kulsum (Guidance and counseling the university of Prof. Dr. Hazairin. SH, 2024)
Empathy is essential for people working in various fields of life, such as business, education, medicine and more. Conversely, not having empathy can lead to criminality in various forms, such as psychopathic violence, rape, and child trafficking. Teachers and prospective teachers, therefore, must have the ability to instill empathy. This study aims to understand the various strategies and factors that influence the cultivation of empathy. The method used is the Participatory Action Research (PAR) approach, which is a process of activities carried out in a participatory manner in learning with students. Direct involvement to conduct field observations, socialization and strengthening empathy towards students. The results showed that the cultivation of empathy can be done by first, increasing self-awareness through reflection on the various experiences that each student has; second, honing active listening skills; third, observing and recognizing children's emotions; and fourth, reading literature and case studies. While the challenge factors that need to be understood in strengthening the empathy of PIAUD students are emotional balance; lack of practical experience; and academic stress, namely the pressure of academic duties and responsibilities.